Transcutaneous drug delivery by liposomes using fractional laser technology. Issue 5 (19th December 2016) - Fujimoto, Takahiro; Wang, Jian; Baba, Kazuki; Oki, Yuka; Hiruta, Yuki; Ito, Masayuki; Ito, Shinobu; Kanazawa, Hideko
Abstract : Objective: Transdermal delivery of hydrophilic peptides remains a challenge due to their poor cellular uptake and transdermal penetration. We hypothesize that combination of a CO2 fractional laser to enhance percutaneous absorption and liposomes as transdermal carriers would improve skin penetration of hydrophilic drugs. Study Design: NA. Methods: Liposomes were prepared using membrane fusion lipid dioleoylphosphatidylethanolamine, and used to deliver 5‐carboxyfluorescein (CF) and fluorescein isothiocyanate‐conjugated ovalbumin (OVA‐FITC) as model hydrophilic peptide drugs. Liposome size was estimated by dynamic light scattering. Liposome uptake into murine macrophage cells and penetration or permeation into Yucatan micropig skin after irradiation by CO2 fractional laser at varying energy levels (laser power and exposure duration) were investigated using Franz cell and fluorescence microscopy. Oxidative damage to the irradiated mouse skin was assessed by electron spin resonance. Results: Size of CF and OVA‐FITC encapsulated liposomes was 324 ± 75 nm. Cellular uptake of OVA‐FITC delivered by liposomes was 10‐fold higher (1, 370 relative fluorescence units, RFU) than delivered in solution form (130 RFU). Fractional laser irradiation increased skin permeation rate of CF liposomes (0–10%) and OVA‐FITC liposomes (4–40%) in a dose‐dependent manner. Although peeling off the stratum corneum facilitated CF liposome penetration at low energy levels (2.69–3.29 J/cm 2 ; 10–20 W for 500 μs), drug permeation was similar (7–8%) in peeled or untreated skin at higher laser energy levels (6.06 J/cm 2 ; 20 W for 1, 500 μs). FITC penetrated deeper in the skin after laser irradiation. However, OH, O 2 −, and VC reactive oxygen species were generated upon irradiation of the skin with a fractional CO2 laser. Conclusions: Increasing laser power and irradiation, time increased liposome uptake by cells and penetration of peptide drugs across the skin in a dose‐dependent manner. High‐energy CO2 fractional laser overcomes the rate‐limiting barrier function of the stratum corneum. Further investigations are required to establish the safety and efficacy of fractional laser‐irradiation assisted delivery of liposome‐encapsulated drugs as a transcutaneous drug delivery system. Lasers Surg. Med. 49:525–532, 2017. © 2016 Wiley Periodicals, Inc.